Left ventricular performance in alcoholic patients without chronic liver disease. Issue 4 (October 1987) - Kelbaek, H; Nielsen, B M; Eriksen, J; Rabøl, A; Christensen, N J; Lund, J O; Bonnevie, O; Munck, O; Godtfredsen, J
Abstract : Left ventricular performance was studied non-invasively in 24 chronic alcoholics without liver disease. Twelve patients who had abstained from drinking for at least one month (group A) and 12 sex and age matched patients who had ceased drinking during the preceding 24 hours (group B) were studied at rest and during 50% submaximal exercise. Cardiac output and stroke volume were measured by first passage and left ventricular ejection fraction by multigated radionuclide cardiography. Twelve healthy sex and age matched controls were also studied. Haemodynamic variables were similar in group A and the controls, except that in group A left ventricular end systolic volume index did not decrease during exercise. In group B the heart rate was increased both at rest and during exercise and plasma noradrenaline concentrations were increased. The stroke volume index did not increase significantly during exercise in group B. In addition, the increase in left ventricular ejection fraction was smaller in group B than in controls. End systolic contraction was reduced in group B patients and diastolic blood pressure was increased. These results suggest that cardiac abnormalities in chronic alcoholics may be reversed after cessation of drinking if no chronic liver disease is present. Recent alcohol consumption increases sympathetic nervous activity, impairs cardiac contractility, and increases afterload during physical stress.